Jeevavanarula mariyu sambandhita parijnanam - (:unkn) unknown (Telangana State Biodiversity Board National Biodiversity Authority, India, 2016)
Its about diversity in nature for taking care of nature by using proper rules & regulations
Keywords: Telugu; Biodiversity; Telugu; Telugu